(untitled) (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Datu AM, Natzir R, Yustisia I, Wahid I, Soraya GV, Kadir S. 2023. Molecular detection and analysis of dengue virus genetic diversity in North Sulawesi, Indonesia during 2022. Biodiversitas 24: 3407-3413. Dengue is a highly infectious disease caused by the dengue virus, consisting of four serotypes (DENV1-DENV4). The existence of diverse serotypes and genotypes in an area significantly impacts the degree of virulence in humans, clinical manifestation, and the epidemiology of the disease. Studying virus diversity in an area is pivotal, especially in dengue-endemic areas such as North Sulawesi. This study was an explorative research analyzing dengue virus serotypes and sequencing on the C-PrM protein region to determine the genetic diversity. This study was conducted on children and adults in 3 health centers in North Sulawesi, Indonesia, in 2022. Of 137 sera samples from febrile patients with dengue-like symptoms, ten were confirmed positive for dengue virus. Out of the ten positive samples, DENV1 was the dominant serotype, which was 70%. This was followed by 20% DENV2 and 10% DENV4. The genotype of each serotype, DENV1, DENV2, and DENV4, was respectively classified into genotype I, cosmopolitan genotype, and genotype I as a new genotype of DENV4 reported in North Sulawesi. This study provides the latest data on the serotypes and genotypes of dengue viruses in North Sulawesi. Molecular surveillance of the dengue virus in North Sulawesi must be continuously conducted due to the circulation of multiple serotypes and genotypes in this province.